2020
DOI: 10.1111/joor.13021
|View full text |Cite
|
Sign up to set email alerts
|

Verification of the criteria for reduced occlusal force to diagnose oral hypofunction in older Japanese people: A prospective cohort study on incident functional disability

Abstract: In 2016, the Japanese Society of Gerodontology (JSG) proposed the concept of “oral hypofunction (OHF),” and recommended two initial criteria for reduced occlusal force (ROF): <200 N of maximum occlusal force (MOF) and < 20 remaining teeth. However, the JSG stated that these criteria need to be reviewed by accumulating further evidence. To examine the validity and equivalence of the two criteria for ROF in the diagnostic criteria for OHF by using the incidence of functional disability as the outcome. This study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…37 , 38 The median tongue pressure in the current older sample was 29.1 kPa, and again, there was no significant functional impairment in relation to mastication, swallowing or speech. Recently, there is also emerging research that the cut‐off values of the diagnosis for oral frailty may need to be revisited for Japanese samples, 39 and the current results demonstrate that these thresholds cannot be applied without further research to German mother‐tongue speakers. This is a clear indication that cut‐off values to differentiate oro‐facial fitness from oro‐facial hypofunction need to be found for groups of different language use and maybe even ethnic background.…”
Section: Discussionmentioning
confidence: 93%
“…37 , 38 The median tongue pressure in the current older sample was 29.1 kPa, and again, there was no significant functional impairment in relation to mastication, swallowing or speech. Recently, there is also emerging research that the cut‐off values of the diagnosis for oral frailty may need to be revisited for Japanese samples, 39 and the current results demonstrate that these thresholds cannot be applied without further research to German mother‐tongue speakers. This is a clear indication that cut‐off values to differentiate oro‐facial fitness from oro‐facial hypofunction need to be found for groups of different language use and maybe even ethnic background.…”
Section: Discussionmentioning
confidence: 93%
“…2,3 Similarly, relationships between physical performance and tongue strength 4,5 and between oral frailty and nutritional status 6,7 have been reported. In longitudinal studies, a reduction in maximum bite force 8,9 and a decrease in the number of remaining functional teeth 10 in older adults have been associated with the development of physical frailty. Accumulated oral frailty can predict not only subsequent physical frailty but also the onset of adverse events such as disability and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…If the management period for OHF had been longer, or if the second assessment had been later, different contributing factors relating to dental treatment may have been found. From another point of view, previous cross‐sectional studies have shown that reduced occlusal force may be associated with the risk of various adverse health outcomes in older people, such as impaired nutritional status, reduced physical function, falls, frailty and functional disability, 23,31–34 while longitudinal model studies have revealed that reduced occlusal force can be a risk factor for subsequent frailty and long‐term care certification 5–8 . These findings suggest that assessing occlusal force can be an important clinical point not only for OHF, but also for physical functions.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulated oral frailty, defined by fewer remaining teeth, reduced masticatory function, poor oral motor function and reduced tongue pressure, may increase the risk of physical frailty, long‐term care and death 2 . Previous studies have reported the number of remaining teeth to be associated with physical frailty, 3,4 and that decreased occlusal force was related to cognitive decline, 5 physical frailty 6 and long‐term care certification 7,8 . A decline in oral function may possibly affect subsequent physical frailty in the older population 9 ; therefore, it may be important to detect signs of oral frailty in its early stages and deal with functional deterioration in the field of clinical dentistry.…”
Section: Introductionmentioning
confidence: 99%